Pre-treatment Serum HE4 Level as a Novel Independent Prognostic Biomarker for Uterine Cervical Carcinoma Patients - Bignotti, Eliana; Zanotti, Laura; Todeschini, Paola; Zizioli, Valentina; Romani, Chiara; Capoferri, Davide; Tognon, Germana; Sartori, Enrico; Calza, Stefano; Odicino, Franco; Ravaggi, Antonella (Frontiers in Oncology, 2020)
In spite of the effective implementation of screening programs, uterine cervical carcinoma (UCC) remains one of the major causes of cancer death among women around the world. The aim of this study was to investigate the prognostic value of serum human epididymis protein 4 (HE4) in UCC. Pre-treatment serum samples from 109 UCC patients and 99 healthy women were analyzed for HE4 levels by a quantitative chemiluminescent microparticle immunoassay on the automated ARCHITECT instrument. HE4 serum (sHE4) levels were significantly higher in UCC patients, regardless of tumor stage, compared with healthy controls. Elevated sHE4 levels were significantly associated with advanced FIGO stage and absence of disease-free interval after treatment. In univariate analysis, higher sHE4 levels were significantly correlated with shorter overall survival and progression-free survival. In multivariate analysis, sHE4 retained its significance as independent adverse prognostic factor for both survival endpoints. This study indicates that HE4 is associated with a more aggressive tumor phenotype and a worse patient’s prognosis. These results suggest the potential role of sHE4 as a novel prognostic marker and as an indicator of high-risk UCC patients for a tailored surgical and adjuvant therapy.